2011
DOI: 10.1007/s10072-011-0709-y
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Chiari malformation: who, when and how

Abstract: There is no effective alternative to surgery in the treatment of the symptomatic cases of chiari malformation. Nonetheless, in literature there is no unanimous consensus about what is the surgical "gold standard" and which are the candidates for surgery. No doubt that intracranial hypertension and ventricular dilatation have to be investigated and treated before considering decompression. It is also very important to keep in mind that a surgery does not guarantee a complete recovery from every symptoms. We rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…[4][5][6][7][8][9][10] Arnold-Chiari malformation is most often a congenital abnormality. Symptoms appear as the patient ages; it is more frequent in females than males with a 3:1 ratio, with an age range of 6 to 60 and a peak diagnosis age of 40 years.…”
Section: Wwwjournalchiromedcommentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7][8][9][10] Arnold-Chiari malformation is most often a congenital abnormality. Symptoms appear as the patient ages; it is more frequent in females than males with a 3:1 ratio, with an age range of 6 to 60 and a peak diagnosis age of 40 years.…”
Section: Wwwjournalchiromedcommentioning
confidence: 99%
“…1,10 Confirmation of ACM can only be made with imaging, most often made by cervical magnetic resonance imaging (MRI), which is the criterion standard; however, this is also seen on brain MRI, computed tomography, and cervical computed tomography. 8 With the increased prevalence of MRI and decreasing cost, there has been an increase in the diagnosis of ACM. 9 Current treatment of ACM varies greatly and is dependent on the discipline of the health care provider.…”
Section: Wwwjournalchiromedcommentioning
confidence: 99%
“…12 Although posterior decompression for symptomatic CM-I is the current treatment standard, a subset of patients with significant ventral cervicomedullary compression has raised the question of whether ventral decompression with or without posterior fusion should be considered in the CM-I population. 6,17 There has been recent interest regarding the impact of posterior odontoid inclination in CM-I, and radiographic studies in the pediatric population have demonstrated an association between CM-I and posterior odontoid inclination. 20 Normative values for odontoid inclination in the adult population have only recently been established.…”
mentioning
confidence: 99%
“…21 Although speculative, it has also been suggested that the relative instability between the cerebellar tonsils and the foramen magnum (because of the small posterior fossa) with intermittent block of CSF flow contributes to ligamentous enlargement, which may be reflected in a larger amount of peri-odontoid tissue. 6 Established craniovertebral junction measurements state that a clivus-canal angle < 150° is abnormal regard- less of patient positioning, and at angles < 150° there is a known increased risk of ventral cervical spinal cord compression. 18 A decrease in the clivus-canal angle is a described feature of basilar invagination, a developmental finding associated with basiocciput hypoplasia.…”
mentioning
confidence: 99%
See 1 more Smart Citation